Pengaruh Customer Satisfaction, Brand Trust, dan Customer Feedback Terhadap Customer Loyalty Pada Perusahaan Mobil Suzuki - Arianto, Jhony Putra Satria (AL-QARDH, 2016)
The background of this research to understand the importance of customer satisfaction will result customer loyalty on consumerâs of automobile. The design of this research applies a research model based on consumerâs of Suzuki Ertiga In Suzuki Indonesia Company which locard in East Bekasi. A total of seventy consumers as respondents were analyzed using multiple regression analysis with SPSS 17. The objectives of this research to examine the importance will result on customer retention and generation of positive word of mouth. The result of this research that the effect of positively Customer Satisfaction, Brand Trust, dan Customer Feedback toward Customer Loyalty. Â The managerial implication for marketing managers for understanding the importance of customer loyalty to increase company profitability.